2005
DOI: 10.2355/isijinternational.45.1452
|View full text |Cite
|
Sign up to set email alerts
|

Development of a Visual Information Technique of Nonstationary Fluctuations in a Blast Furnace Process

Abstract: Fig. 1. Relationship between the phenomena and causes of operating condition disorder.and three-dimensional nonstationary physical models in particular, have been being developed in recent years in an attempt to quantitatively evaluate and analyze nonstationary phenomena (dynamic behaviors and characteristics). Quantitative analysis and control techniques were also developed by applying AI. [12][13][14][15][16][17] Despite the progress of such physical models and AI, and the development in the varieties of sen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2010
2010
2018
2018

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(2 citation statements)
references
References 14 publications
0
2
0
Order By: Relevance
“…To control the horizontal falling speed and the falling width of the burden materials from the rotating chute, a new type of chute, which is equipped with a repulsion plate at the chute end, was developed and put into practical use. 151,152) All companies developed bell-less burden distribution models in order to take advantage of the high flexibility of bell-less systems in control of burden distribution. 153,154) Using one such model, Kajiwara et al 155) showed that flat charging, which bell-MA charging systems cannot achieve, is possible with bell-less blast furnaces.…”
Section: Bell-less Charging Systemsmentioning
confidence: 99%
See 1 more Smart Citation
“…To control the horizontal falling speed and the falling width of the burden materials from the rotating chute, a new type of chute, which is equipped with a repulsion plate at the chute end, was developed and put into practical use. 151,152) All companies developed bell-less burden distribution models in order to take advantage of the high flexibility of bell-less systems in control of burden distribution. 153,154) Using one such model, Kajiwara et al 155) showed that flat charging, which bell-MA charging systems cannot achieve, is possible with bell-less blast furnaces.…”
Section: Bell-less Charging Systemsmentioning
confidence: 99%
“…In the 2000s, Nippon Steel developed a visualization system called VENUS 175) which graphically shows stave temperature profiles by creating an isothermal diagram, making it possible to learn the blast furnace radial and vertical heat load distribution of the furnace wall. VENUS serves as an operation improvement tool by combining these time-series transition data with similar information from the past and applying the results to early identification of gas flow problems inside the furnace, to estimating the cohesive zone root, and to other operation analysis problems.…”
Section: Artificial Intelligence (Ai) and Other Operationmentioning
confidence: 99%